Schedule Optimization of Time-Triggered Systems Communicating Over the FlexRay Static Segment - Haibo Zeng; Di Natale, M; Ghosal, A; Sangiovanni-Vincentelli, A (IEEE transactions on industrial informatics, 2011)
FlexRay is a new high-bandwidth communication protocol for the automotive domain, providing support for the transmission of time-critical periodic frames in a static segment and priority-based scheduling of event-triggered frames in a dynamic segment. The design of a system scheduling with communication over the FlexRay static segment is not an easy task because of protocol constraints and the demand for extensibility and flexibility. We study the problem of the ECU and FlexRay bus scheduling synthesis from the perspective of the application designer, interested in optimizing the scheduling subject to timing constraints with respect to latency- or extensibility-related metric functions. We provide solutions for a task and signal scheduling problem, including different task scheduling policies based on existing industry standards. The solutions are based on the Mixed-Integer Linear Programming optimization framework. We show the results of the application of the method to case studies consisting of an X-by-wire system on actual prototype vehicles.